RECORD OF THE PEA-CRAB Calyptraeotheres garthi (FENUCCI, 1975) (BRACHYURA, PINNOTHERIDAE) IN TROPICAL ATLANTIC OCEAN - Bezerra Ribeiro, Felipe; Matthews-Cascon, Helena; Ernesto Arruda Bezerra, Luis (Arquivos de Ciências do Mar, 2020)
This study reports the occurrence of the pea-crab Calyptraeotheres garthi (Fenucci, 1975) for the State of Ceará, Northeastern Brazil. The crab was found associated to the calyptraeid limpet Crepidula plana (Say, 1822) in a Voluta ebraea (Linnaeus, 1758) shell occupied by the hermit crab Petrochirus diogenes (Linnaeus, 1758). This record represents the northernmost occurrence for the species in the Atlantic Ocean and the second for Brazilian waters. This new record increases the distribution area of C. garthi in about 3520 km. Taxonomic and biogeographic remarks, ecological notes and an updated distribution map are provided for this species.